Targum Pseudo-Jonathan and Late Jewish Literary Aramaic - Kaufman, Stephen A. 194X- (Aramaic studies, 2013)
The twentieth-century’s Targum manuscript discoveries made clear that if Neofiti, the Fragment Targums, and the Cairo Geniza fragments were composed in Jewish Palestinian Aramaic, then Targum Pseudo-Jonathan was not. In this classic essay, originally written in Hebrew in 1985–1986 and translated here for the first time, Stephen Kaufman worked to describe Pseudo-Jonathan’s dialect. He found that it borrowed from other dialects, but merged them into a single unified dialect appearing not only in Pseudo-Jonathan, but also in several Writings Targums. This essay thus presented the earliest description of Late Jewish Literary Aramaic.